A reputation-based truthfulness paradigm for multi-hop transmission in cognitive radio networks. (25th September 2019) - Limbasiya, Trupil; Das, Debasis; Yadav, Ram Narayan
Cognitive radio networks (CRNs) consist of different intellectual users with capability of sensing and sharing underutilised spectrum, and they are called as cognitive users (CUs). The spectrum is allocated to licensed users or primary users (PUs), but they do not utilise it completely. To overcome an ever-increasing spectrum demand and utilise the underutilised licensed spectrum, the cognitive radio plays a major role. In this distributed network, communications among CUs become more challenging due to channel heterogeneity, uncontrolled environment, a need of cooperative and accurate sensing, and different security attacks. Thus, this affects and degrades system and CRN performance, which creates an opportunity for a trust management model to manage the CRNs properly. In this paper, we propose an efficient trust management protocol for centralised and distributed CRNs to build a trust-based system over the complete cognitive cycle to protect against security attacks brought by the unreliable individuals. The security analysis and simulation results represent that the proposed protocol can identify malicious behaviour and thus, it enhances reliability of the network in centralised and distributed circumstances.